Pembelajaran Fisika Kontekstual Berbasis Nilai Islami untuk Menumbuhkan Sikap Ilmiah Siswa - Rita Nurmayanti Amas (CV. Intake Pustaka, 2026)
This study aims to analyze the effectiveness of contextual physics learning based on Islamic values in fostering students’ scientific attitudes in madrasah. The research employed a quantitative approach with a quasi-experimental method using a pretest–posttest control group design. The participants consisted of 68 eleventh-grade students of Madrasah Aliyah Negeri 1 Karawang, divided into experimental and control groups. The experimental class received contextual physics learning integrated with Islamic values such as honesty, responsibility, curiosity, and love of knowledge, while the control class was taught through conventional methods. Data were collected using a scientific attitude questionnaire, learning activity observation sheets, and lesson implementation sheets, and analyzed using an independent t-test and normalized gain (N-gain). The results showed a significant improvement in the experimental group’s scientific attitudes, with an N-gain score of 0.62 (moderate–high category), compared to the control group’s 0.28 (low category). The integration of Islamic values within contextual learning effectively enhanced students’ curiosity, responsibility, and appreciation for the harmony between scientific and spiritual understanding. Therefore, contextual physics learning based on Islamic values can serve as a strategic alternative for developing scientific attitudes and character in madrasah students in a holistic manner.